Efektivitas Pembelajaran PAK Menggunakan Metode PJBL Fase D Kelas VII SMP Yoannes XXIII Semarang - Bangkit Setio Adi; Andarweni Astuti; Gregorius Daru Wijoyoko (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
Many educational institutions still rely on uniform instructional methods, which often diminish student motivation, cause feelings of monotony, hinder knowledge development, lower academic performance, and limit opportunities for creative exploration. This study aims to: (1) assess the effectiveness of the Project-Based Learning (PJBL) model compared to traditional lecture-based instruction in enhancing student achievement; (2) investigate the influence of PJBL on students' creativity relative to the lecture method; and (3) examine the extent to which creativity contributes to overall learning outcomes. This research uses an experimental design comparing two groups of students: one taught using the PJBL model and the other using traditional lecture-based instruction. Data were collected through achievement tests, questionnaires, and observations of students' creative works. The results show that students who engaged in PJBL-based learning showed significant improvement in both academic performance and creativity compared to those in the lecture-based learning group. Additionally, creativity was found to positively contribute to overall learning outcomes. This study suggests that the implementation of the PJBL model can be an effective alternative to enhance student motivation, academic performance, and creative skills.